Apnoeic oxygenation with high‐flow nasal oxygen for laryngeal surgery: a case series. (19th October 2017) - Lyons, C.; Callaghan, M.
Summary: Surgery under apnoeic conditions with the use of high‐flow nasal oxygen is novel. Between November 2016 and May 2017, 28 patients underwent tubeless laryngeal or tracheal surgery under apnoeic conditions with high‐flow nasal oxygen as the sole method of gas exchange. Patients received total intravenous anaesthesia and neuromuscular blocking agents for the duration of their surgery. The median (IQR [range]) apnoea time was 19 (15–24 [9–37]) min. Four patients experienced an episode of oxygen desaturation to a value between 85% and 90%, lasting less than 2 min in each case. Median (IQR [range]) end‐tidal carbon dioxide (ETCO2 ) level following apnoea was 8.2 (7.2–9.4 [5.8–11.8]) kPa. The mean (SD) rate of ETCO2 increase was 0.17 (0.07) kPa.min −1 from an approximated baseline value of 5.00 kPa. Venous blood sampling from 19 patients demonstrated a mean (SD) partial pressure of carbon dioxide (PV CO2 ) of 6.29 (0.71) kPa at baseline and 9.44 (1.12) kPa after 15 min of apnoea. This equates to a mean (SD) PV CO2 rise of 0.21 (0.08) kPa.min −1 during this period. Mean (SD) pH was 7.40 (0.03) at baseline and 7.23 (0.04) after 15 min of apnoea. Mean (SD) standard bicarbonate was 26.7 (1.8) mmol.l −1 at baseline and 25.4 (1.8) mmol.l −1 at 15 min. We conclude that high‐flow nasal oxygen under apnoeic conditions can provide satisfactory gas exchange in order to allow tubeless anaesthesia for laryngeal surgery.